Esthetic management of early childhood caries in primary maxillary anterior teeth comprising a supplemental tooth - Namratha Tharay; Sivakumar Nuvvula (SRM Journal of Research in Dental Sciences, 2016)
Early childhood caries (ECC) is a severe problem in the children that necessities the pulpal and/or esthetic restorative management. Primary supplemental teeth associated with its succedaneous permanent teeth is a rare dental anomaly. Both the ECC and supplemental teeth predispose for the early intervention that influence the esthetic, physiological, and psychological factors. Hence, the present paper reports a 2 years 10 months boy with severe ECC and the presence of primary maxillary supplemental tooth associated with its succedaneous tooth, symptomatically and esthetically managed with wire posts and strip crowns. The present paper also discusses a brief review of supernumerary teeth regarding its prevalence, theories and management of the same.